The management of hyperlipidaemia: are specialist lipid clinics needed? - Roche, M; Grice, D; Neil, H; Matthews, DR (1992)
A survey of all general practitioners in Oxfordshire was undertaken to determine what use they wanted to make of a district lipid clinic, and to assess how effectively it met their needs. The response rate was 85% (288/340) but some respondents failed to answer each section of every question. One hundred and eighty-five general practitioners (64%) had previously referred patients to the clinic. Most respondents selectively asked for blood cholesterol measurements in patients with major cardiovascular risk factors (94%, 266/283), and few routinely asked for cholesterol as part of a health check (17%, 43/258). Most thought that referral to a clinic was appropriate for children (65%, 149/229), for patients aged 20 to 39 (85%, 209/247), and for older patients aged up to 60 (77%, 186/243). Ninety-four per cent (260/277) wanted access to specialist advice for patients with a cholesterol concentration exceeding 8.0 mmol l-1, and 73% (197/270) wanted specialist advice before starting treatment with a lipid-lowering drug. Although most respondents rated the service provided by the clinic favourably, more than half would have liked more information on prognosis, drug treatment, long-term follow-up, and screening of family members. We conclude that general practitioners would like access to specialist advice for the management of severe hyperlipidaemias, and that cardiovascular screening programmes in primary care have important resource implications for specialist services.